(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
Traceability in the feed sector lies in the aspects of food safety, ethics and commercial responsibility. This paper answers the question: "How to propose a method of traceability in a system that has many vulnerabilities in its processes?". Through knowledge of the process, it was possible to map it and identify the vulnerabilities that exist in it, and thus define a contingency plan to minimize and/or remedy the identified risk events. Following the improvements, a traceability approach was proposed.